HEADLESS COMPRESSION SCREW FOR SURGICAL TREATMENT OF SCAPHOID FRACTURES - Kostov, Hristijan; Gavrilovski , Andreja; Merdzanoski , Igor; Spasov , Marko; Gjorikj Petrushevka , Magdalena; Mihajlova Ilie , Radmila Mila (Sanamed, 2024)
Introduction: Scaphoid bone fractures are common and present unique challenges due to the bone’s specific fracture patterns and vascular supply. Prompt diagnosis and treatment of acute scaphoid fractures are crucial to prevent nonunion and subsequent wrist arthritis. While non-displaced fractures can often be managed conservatively, advancements in diagnostics, surgical techniques, and implant materials have driven an increasing preference for early surgical fixation. Patients and Methods: Over a 12-month period, 10 male patients with scaphoid fractures underwent surgical treatment at the University Clinic of Traumatology in Skopje, from January 2022 to March 2024. The patients’ mean age was 27.3 years. Diagnosis was confirmed using CT scans and X-rays, with four fractures affecting the left hand and six the right. All patients underwent open reduction and internal fixation using a headless compression screw. A volar approach was used in nine cases, and a dorsal approach in one. Six patients were treated surgically within 4–14 days post-injury, while four were treated for nonunion after previous conservative management. Among these four, two presented at three months and two at seven months post-injury. The latter group required spongyoplasty and osteosynthesis due to scaphoid deformity, resorption, and bone loss. Results: Patients were followed up at 1, 3, 6, and 12 months post-surgery. Physical therapy commenced four weeks after surgery, and radiographic monitoring continued until fracture healing was confirmed. No cases of wrist osteoarthritis were observed during the follow-up period. Conclusion: Although this study represents a small series, it highlights the importance of individualized clinical decision-making for scaphoid fractures. Early surgical intervention can enhance comfort, facilitate quicker return to daily activities, and reduce immobilization duration.